Correlation and regression analysis of the body measurements of the Doro Ncanga Buffalo (Bubalus bubalis) reared extensively in the Savanna of Mount Tambora Dompu Regency, Indonesia - Husni Husni; Maskur Maskur; Chairussyuhur Arman (Aceh Journal of Animal Science, 2018)
The objectives of the present study were examined the correlation and regression of body measurements of the Doro Ncanga buffaloes in the Savanna of Mount Tambora Dompu Regency, Indonesia. A total of 339 animals were used in this study. In female, body weight (BW) was found to be significantly (p0.05) correlated with body length (BL), the degree of correlation increased from 0-6 (r=0.319) to 13-24 months (r=0.394), thereafter decreased at 36 months (r=0.160). The BW was not significantly correlated with height at wither (HW) for all 5 age groups. However, BW and heart girth (HG) were highly correlated (p0.01) between age groups 0-6 (r=0.967) and 36 months (r=0.978). The BL was significantly (p0.01) correlated with HW from 0-6 to 13-24 months of age, except for 25-36 months of age. The correlation between BL and HG was highly significant (p0.01) at 0-6 (r=0.427) and 13-24 (0.371) months of age, then decreased with the increase of age. The HW had no strong correlation with HG  at all groups. Regression model of BW changes with HG was predictable with R2 values ranged from 0.896 to 0.957. In male, BW had a strong correlations with HG for age groups 0-6 (r=0.979) and 7-12 months (r=0.972). The BL and HW were not highly correlated with BW at all groups. However, BW was significantly (p0.01) correlated with HG for age groups 0-6 (r=0.979) and 7-12 months (r=0.972). Their R2 values were 0.958 and 0.945, respectively. A highly significant (p0.01) correlations were also observed between BL and HW for age groups 0-6 months (r=0.677)and 7-12 months (0.462). The  R2 values were 0.458 and 0.214 for the two different age groups, respectively. The estimates of coefficient of determinations and predictive equations show that HG alone could be used to predict BW of female and male Doro Ncanga buffalo at different age groups.